From ‘Sacred’ To ‘Secular’? The Hermeneutical Future of Religion in The Thought of Gianni Vattimo and Charles Taylor - Narithookkil, Rogi Thomas (Asian Horizons, 2020)
University/Institution: The University of Dundee, Scotland Faculty/Department: Humanities/Philosophy Supervisor of the Doctoral Dissertation: Prof. Nicholas Davey Year of Doctoral Defence: 2018